Factors Affecting BPK Audit Findings on Local Government Financial Reports In West Sulawesi Province For The Period 2020 to 2022. 2022 - Asa Jasmine Harimurti; Jamaludin Iskak (PT. Publikasiku Academic Solution, 2023)
The Supreme Audit Agency (BPK) is the only institution authorized to carry out the task of examining the management and financial responsibility of the state / region in accordance with applicable laws and regulations. Central / local governments are required to submit their financial reports to BPK for examination as a form of responsibility to the people, in this case represented by the House of Representatives (DPR) / Regional People's Representative Council (DPRD). This study aims to determine the factors that influence the number of BPK audit findings on the Internal Control System (SPI) and compliance with applicable laws and regulations. Factors that are examined for their influence in determining the number of BPK audit findings in this study are the size of local government, the level of local wealth, fixed asset procurement, and the complexity of local government. The data used is the Audit Report (LHP) on the examination of regional financial statements in West Sulawesi Province issued by BPK from 2020 to 2022.